Utilizing Test Item Analysis to Portray the Quality of English Final Test - Nuri Ati Ningsih; Woro Widowati (Universitas PGRI Madiun, 2021)
This study aims at describing the quality of the item test by analyzing the difficulty level, discriminating index, and distractor effectiveness of English final test item. The researchers use a descriptive quantitative as the research design. The population and sample of the study is the student’s answer sheets of the tenth grade of SMK PGRI Wonoasri. There are 22 student’s answer sheet as the primary data. The researchers use documentation technique and test kits of the English final test as the instrument. The data is analyzed by using classical theory measurement and item analysis’ formula. The result shows: (1) the level of difficulty which categorized as difficult is 35% (40 items), medium is 47% (19 items), and easy is 18% (7 items); (2) discrimination index that recommended for being rejected is 15% (6 items), accepted 38% (15 items), and not accepted is 47% (19 items); (3) distractor effectiveness which has functioning distractors as very good is 20% (8 items), good is 43% (17 items), fair 27% (11 items), and less good is 10% (4 items). In short, the quality and acceptance of test items of English final is medium or fair. So, there are still a lot of items need to be revised.